2010
DOI: 10.1289/ehp.1002239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Regulating Lead in Synthetic Turf

Abstract: BackgroundIn 2007, a synthetic turf recreational field in Newark, New Jersey, was closed because lead was found in synthetic turf fibers and in surface dust at concentrations exceeding hazard criteria. Consequently, public health professionals across the country began testing synthetic turf to determine whether it represented a lead hazard. Currently, no standardized methods exist to test for lead in synthetic turf or to assess lead hazards.ObjectivesOur objectives were to increase awareness of potential lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…In general, the levels of VOCs, SVOCs, PAHs, heavy metals, and particulates (PM 2.5 and PM 10 ) in the air above outdoor artificial turf fields were found to be comparable to those of local background, and were within the regulatory limits, 9,46−51 although the results might only be applicable to the specific fields and conditions measured. One study found that the levels of PM 10 and metals at the high play activity sites of artificial turf fields, although elevated compared to the background concentrations, were below the corresponding air quality standards. 46 The VOCs and SVOCs in the air above outdoor artificial turf fields resulted from volatilization from the fields and local traffic emissions, both of which were subject to air dispersion and dilution.…”
Section: ■ Assessing the Environmental Impacts Of Artificial Turfmentioning
confidence: 99%
“…In general, the levels of VOCs, SVOCs, PAHs, heavy metals, and particulates (PM 2.5 and PM 10 ) in the air above outdoor artificial turf fields were found to be comparable to those of local background, and were within the regulatory limits, 9,46−51 although the results might only be applicable to the specific fields and conditions measured. One study found that the levels of PM 10 and metals at the high play activity sites of artificial turf fields, although elevated compared to the background concentrations, were below the corresponding air quality standards. 46 The VOCs and SVOCs in the air above outdoor artificial turf fields resulted from volatilization from the fields and local traffic emissions, both of which were subject to air dispersion and dilution.…”
Section: ■ Assessing the Environmental Impacts Of Artificial Turfmentioning
confidence: 99%
“…Grass-like surfaces are extensively used for blanket lawns, park spaces, and athletic fields where children and adults relax and play, but a number of questions regarding their potential effects on health and environment are still largely unanswered (Birkholz et al 2003;Whitlock 2008;EPA 2009;Simon 2010;Van Ulirsch et al 2010;Ginsberg et al 2011;Serensits et al 2011;Ruffino et al 2013;Cheng et al 2014). The main sources of concern regard the use of rubber granulates as infill material (Claudio 2008;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It should also be considered that in outdoor environments, rubbers are exposed to oxidizing agents, light, temperature, and rain; these conditions may reduce their mechanical resistance and enhance the release of toxic agents (Zhang et al 2009;Cheng et al 2014). Further studies should thus address the behavior of these materials under unfavorable conditions, also considering that children are the most affected population (Van Ulirsch et al 2010;Ginsberg et al 2011;Kim et al 2012;Cheng et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Again, no elevated health risks were identified in air samples collected from on‐field or downwind locations . In addition to organic compounds, metals have been identified as a potential contaminant of concern, particularly lead, which can cause severe permanent neurological health effects in children . Lead‐based coloring agents used in fibers of some artificial turf can be released into the environment as the field ages.…”
Section: Introductionmentioning
confidence: 99%
“…Lead‐based coloring agents used in fibers of some artificial turf can be released into the environment as the field ages. Measured concentrations have exceeded the statutory lead limit for consumer products intended for children and EPA lead‐dust standard for floors …”
Section: Introductionmentioning
confidence: 99%